Crescimento, produtividade e qualidade das frutas de morangueiro em hidroponia: efeito da concentração de nutrientes e da densidade de plantio. - Portela, Isabelita Pereira (2011)
The strawberry crop presents great importance for the Horticulture sector of the Southern part of Rio Grande do Sul due to its high yield and economic income, once the fruit has guaranteed market and high marketable price. Hydroponic cultivation allows optimizing the greenhouse vertical area, leading to a higher yield, reduces the diseases occurrence and also makes easier crop management and, as a consequence, enhances farmer life quality. However, there are few studies on the adaptation of the crop to this cultivation system, especially focusing concentrations of the nutrient solution and, overall, plant densities. Aiming to study growth, yield and fruit quality of strawberry crop in hydroponics system, two trials were conducted in a plastic greenhouse at Universidade Federal de Pelotas , RS. NFT (nutrient film technique) hydroponic system was employed. It consists of cement tiles cultivation benches. The first trial aimed to study different ionic concentrations of the nutrient solution for cultivar Camarosa and was replicated in two consecutive years (2009/2010). The analyzed experimental factor was the nutrient solution electrical conductivity (EC) at four levels: 0.9, 1.5, 2.1, 2.7dS m-1 (2009) and five levels: 0.7, 1.2, 1.7, 2.2, 2.7 dS m-1 (2010). The second trial was conducted in order to verify the effect of different plant densities on cultivar Camino Real. The experimental factor was plant density at four levels: 15.0, 12.5, 10.7, and 9.3 plants m-2. Fresh and dry matter of leaves, crown, roots and fruit, leaf area, fruit number and average fruit weight were evaluated. Samples of fruits were analyzed regarding to total soluble solids content (TSS), titratable total acidity (TTA)  for both trials of 2010  concentrations of anthocyanins, L-ascorbic acid, total phenolics compounds and 12 antioxidant capacity only for EC trial in 2010. The obtained results of the first trial indicated that EC from 1.2 to 1.5dS m-1 promotes plant growth and fruit yield. Growth and yield decreased when EC is below or above these values. The fruits total soluble solids content, antocyanin and L-ascorbic acid concentrations were increased at 1.7dS m-1 EC. The concentration of total phenolic compounds was increased reducing the EC to 1.2dS m-1. While soluble solids, anthocyanin and L-ascorbic acid content, respectively, decreased by 17, 17 and 15%, fruit yield was increased by 52% and phenolic compounds concentration by 22 %, when the EC decreased from 1.7 to 1.2dS m-1.The average fruit weight was reduced with increasing EC in 2009 and it was not affected in 2010, as well as the acidity and the antioxidant capacity. We can conclude that nutrient solution from 1.2 to 1.5 dS m-1 EC can be used to achieve higher yieldy, without great losses in fruit quality of cultivar Camarosa grown in NFT hydroponic system. The results obtained from the second trial indicated that growth and yield of individual plants of strawberry cultivar Camino Real was not affect by increasing plant density in the rage from 9.3 to 15.0 plants m-2. Growth and yield per square meter, as well as chemical characteristics related to the organoleptic quality of fruits (TSS and TSS/TTA), present linear response to increasing plant density. We suggest the adoption of the plant density of 12.5 plants m-2, which provides high yield, with appropriate organoleptic characteristics of fruits, and reduction in the number of plants required in relation to 15.0 plants m-2 plant density. However, it is necessary to carry out additional studies on cultivar Camino Real in order to promote changes in the system and its management and check the economic feasibility of its cultivation in hydroponics.